NEUROPSYCHOLOGICAL AND SOMATIC COMPLICATIONS OF ELECTROCONVULSIVE THERAPY (ECT) – A REVIEW OF CURRENT EVIDENCE AND CLINICAL IMPLICATIONS - Martyna Stanik; Elżbieta Trzyna; Klaudia Jurkowska; Joanna Górak; Eleonora Y. Mahoney; Ewa Bełc; Agata Reliszka; Aleksandra Stadnik; Anna Gliwa; Anastazja Gibowska (International Journal of Innovative Technologies in Social Science, 2026)
Electroconvulsive therapy (ECT) remains one of the most effective treatment modalities for severe psychiatric disorders, particularly treatment-resistant depression, catatonia, and schizoaffective disorders. Despite its well-established efficacy, ECT continues to generate controversy due to the potential for neuropsychological and somatic complications. The aim of this review is to provide a comprehensive analysis of ECT-related complications, incorporating the latest scientific findings, underlying mechanisms of cognitive deficits, risk factors, and strategies to minimize adverse effects. Evidence indicates that most cognitive deficits are transient; however, they necessitate careful monitoring, meticulous premedication, and individualized treatment planning in clinical practice.